2022
DOI: 10.21037/tlcr-22-225
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of amrubicin therapy after chemoimmunotherapy in small cell lung cancer patients

Abstract: Background: Although the addition of immune checkpoint inhibitors (ICIs) to platinum-doublet chemotherapy has improved the efficacy of first-line therapy in extensive-disease small cell lung cancer (SCLC) patients, the best treatment option for patients with recurrent SCLC has not yet been determined.We conducted a retrospective study to evaluate the efficacy and safety of amrubicin (AMR) therapy after treatment with ICIs. Methods:We retrospectively assessed patients with recurrent SCLC who received AMR after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The IMPOWER133 trial showed that adding ICIs to carboplatin and etoposide improved survival in patients with ES‐SCLC compared to chemotherapy alone 21 . However, other trials failed to show any benefit of ICIs as a second‐line treatment for ES‐SCLC 22–25 . Thus, it seems that the efficacy of ICIs is mainly observed during the first‐line treatment and that subsequent ICI therapy may not be effective for patients who did not respond to first‐line ICI plus chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IMPOWER133 trial showed that adding ICIs to carboplatin and etoposide improved survival in patients with ES‐SCLC compared to chemotherapy alone 21 . However, other trials failed to show any benefit of ICIs as a second‐line treatment for ES‐SCLC 22–25 . Thus, it seems that the efficacy of ICIs is mainly observed during the first‐line treatment and that subsequent ICI therapy may not be effective for patients who did not respond to first‐line ICI plus chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 21 However, other trials failed to show any benefit of ICIs as a second‐line treatment for ES‐SCLC. 22 , 23 , 24 , 25 Thus, it seems that the efficacy of ICIs is mainly observed during the first‐line treatment and that subsequent ICI therapy may not be effective for patients who did not respond to first‐line ICI plus chemotherapy. Therefore, it is crucial to identify biomarkers that can predict the response to first‐line ICI plus chemotherapy and guide the selection of patients who may benefit from this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, the sequence of chemotherapy following nivolumab in non‐small cell lung cancer enhanced the antitumor activity of cytotoxic chemotherapy. 18 In addition, a recent retrospective study revealed that the efficacy of AMR therapy after chemo‐immunotherapy in patients with SCLC showed an overall response rate of 47% (95% confidence interval [CI]: 30%–64%), and the disease‐control rate of 73% (95% CI: 56%–86%), 19 indicating that single agent of AMR is a useful treatment option after chemo‐immunotherapy. Irinotecan is a topoisomerase I inhibitor and a major chemotherapeutic agent and has been used for treating SCLC for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have assessed the efficacy and safety of AMR for relapsed SCLC after a first-line regimen, including ICI. [50][51][52] An ORR of 47%, median PFS of 3.8 months, and median OS of 10 months was reported. Toxicity was manageable; 73% of patients had grade 3 or 4 neutropenia and only one case (3%) of interstitial lung disease resulting in discontinuation of AMR.…”
Section: Refractory Relapsementioning
confidence: 99%
“…Toxicity was manageable; 73% of patients had grade 3 or 4 neutropenia and only one case (3%) of interstitial lung disease resulting in discontinuation of AMR. 52 …”
Section: Second-line or Later Treatmentmentioning
confidence: 99%